2019
DOI: 10.5603/arm.2019.0029
|View full text |Cite
|
Sign up to set email alerts
|

Is Inhaled Heparin a Viable Therapeutic Option in Inhalation Injury?

Abstract: Inhalation injury is a major cause of morbidity and mortality in patients with burns. Presence of airways injury adds to the need of fluid supplementation, increases risk of pulmonary complications. Due to many mechanisms involved in pathophysiology the treatment is complex. Among them the formation of fibrin casts inside airways constitutes a prominent element. The material residing in tracheobronchial tree causes ventilation-perfusion mismatch, complicates mechanical ventilation, provides a medium for bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Apart from its anti-coagulant effects, a retrospective cohort study found that IL-6 levels were significantly reduced while the percentage of lymphocytes was remarkably increased in the hospitalized COVID-19 treated with LMWH in comparison to the non-LMWH-treated group (Shi et al, 2020b), demonstrating the anti-inflammatory activity of the drug. In addition to the systemic administration, local application of heparin/LMWH through intranasal or inhalation route have also been reported for the treatment of lung diseases and inhalation injury (Yildiz-Pekoz and Ozsoy, 2017;Zielinski et al, 2019). Considering the antiviral activities of heparin/LMWH, along with data suggesting that the nasal epithelium is a portal for initial infection and transmission, Tandon et al suggested that intranasal administration of UFH may be an effective and safe prophylactic treatment SARS-CoV-2 transmission.…”
Section: Current/potential Clinical Applications Of Heparin/hs In Covid-19mentioning
confidence: 99%
“…Apart from its anti-coagulant effects, a retrospective cohort study found that IL-6 levels were significantly reduced while the percentage of lymphocytes was remarkably increased in the hospitalized COVID-19 treated with LMWH in comparison to the non-LMWH-treated group (Shi et al, 2020b), demonstrating the anti-inflammatory activity of the drug. In addition to the systemic administration, local application of heparin/LMWH through intranasal or inhalation route have also been reported for the treatment of lung diseases and inhalation injury (Yildiz-Pekoz and Ozsoy, 2017;Zielinski et al, 2019). Considering the antiviral activities of heparin/LMWH, along with data suggesting that the nasal epithelium is a portal for initial infection and transmission, Tandon et al suggested that intranasal administration of UFH may be an effective and safe prophylactic treatment SARS-CoV-2 transmission.…”
Section: Current/potential Clinical Applications Of Heparin/hs In Covid-19mentioning
confidence: 99%
“…No references were used as evidence. A systematic review examining the effects of heparin inhalation on inhalation injury was reported in 2019; 2 this SR included six observational studies and one RCT, of which two observational studies showed reduced mortality with heparin inhalation, two observational studies showed reduced lung injury score, and one observational study reported shortening of the mechanical ventilation period. The RCT comparing inhaled doses of different heparins reported lower lung injury scores in the high dose (10,000 units every 2 h) group than in the low dose (5,000 units every 2 h) group.…”
Section: Cq2–2mentioning
confidence: 99%
“…An observational study included in the above systematic review reported that heparin inhalation increased the risk of pneumonia 2 . A protocol of inhaling 5,000 or 10,000 units of heparin every 2 or 4 h has not been shown to increase bleeding complications, but it may prolong activated partial thromboplastin time (APTT) and prothrombin time (PT), and its recommended to monitor these parameters 2 . In one RCT, 25,000 units of heparin was inhaled by the treatment group every 4 h, and the study was suspended after 13 cases were registered 3 .…”
Section: Cq2–2mentioning
confidence: 99%
See 2 more Smart Citations